2014
DOI: 10.1186/1471-2407-14-693
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of long non-coding RNA NEAT1 impairs myeloid differentiation in acute promyelocytic leukemia cells

Abstract: BackgroundAcute promyelocytic leukemia (APL) is characterized by the reciprocal translocation t(15;17), which fuses PML with retinoic acid receptor alpha (RARα). Although PML-RARα is crucially important for pathogenesis and responsiveness to treatment, the molecular and cellular mechanisms by which PML-RARα exerts its oncogenic potential have not been fully elucidated. Recent reports have suggested that long non-coding RNAs (lncRNAs) contribute to the precise control of gene expression and are involved in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(166 citation statements)
references
References 30 publications
5
160
1
Order By: Relevance
“…However, downregulation of NEAT1 has been observed in the several other malignancies, including those affecting the liver, retina and esophagus (37). Furthermore, anomalous NEAT1 expression has been reported in various human malignancies, including acute promyelocytic leukemia, where NEAT1 repression was predominant in patients with leukemia caused by promyelocytic leukemia-retinoic acid receptor α (RARα) gene translocation (17). In addition, time-lapse imaging experiments with NEAT1 constructs demonstrated the integral role of NEAT1 expression and paraspeckles formation at the NEAT1 locus (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, downregulation of NEAT1 has been observed in the several other malignancies, including those affecting the liver, retina and esophagus (37). Furthermore, anomalous NEAT1 expression has been reported in various human malignancies, including acute promyelocytic leukemia, where NEAT1 repression was predominant in patients with leukemia caused by promyelocytic leukemia-retinoic acid receptor α (RARα) gene translocation (17). In addition, time-lapse imaging experiments with NEAT1 constructs demonstrated the integral role of NEAT1 expression and paraspeckles formation at the NEAT1 locus (38).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Zeng et al reported that NEAT1 lncRNA is comprised of two isoforms, NEAT1_1 and NEAT1_2 (17). Therefore, the present study compared conservative sequences of the two isoforms using rVista 2.0 (http://rvista.dcode.org/) by performing evolutionary analysis of transcription factor binding sites.…”
Section: Methodsmentioning
confidence: 99%
“…[16] This fusion protein causes a block at the promyelocytic differentiation stage. [17] APL can occur in extramedullary form, and EMI is responsible for 3-8% of cases in relapse. The most common target tissues are CNS and skin.…”
Section: Genetic and Molecular Features Of Extramedullary Infiltratiomentioning
confidence: 99%
“…This lncRNA has been recently revealed to be an architectural component of a subnuclear structure called the paraspeckle, which is suggested to be involved in regulating gene expression by retaining mRNAs for editing in the nucleus (Chen and Carmichael, 2009). Anomalous NEAT1 expression has been reported in human malignancies, including of leukemia and ovarian carcinoma (Kim et al, 2010;Zeng et al, 2014). However, it is not yet fully understood how NEAT1 affects carcinogenesis and biological behavior of NSCLC.…”
Section: Introductionmentioning
confidence: 99%